Small change - Roberts, Sheila (New York : St. Martin's Press, 2014)
Rachel, Jessica and Tiffany have major money problems. Tiffany has a mountain of credit card debt about to come crashing down on her. Jessica's husband lost his job, thrusting this longtime stay-at-home mom out into the workforce. And Rachel's divorce has transformed her from an upper-middle-class mom to a strapped-for-cash divorcee. Together, they start a financial support group called The Small Change Club, challenging each other to bring balance back to their checkbooks, and their lives. They are about to learn some very important lessons: that small changes can make a big difference, and that some things in life, like good friends, are truly priceless.
Keywords: Female friendship -- Fiction; Self-actualization (Psychology) in women -- Fiction; Life change events -- Fiction